Influence of Various Model Compounds on the Rheological Properties of Zein-Based Gels - Gagliardi, Agnese (Molecules, 2020)
The controlled release of a compound entrapped in a biocompatible formulation is a sought-after goal in modern pharmaceutical technology. Zein is a hydrophobic protein which has several advantageous properties that make it suitable for use as a biocompatible and degradable material under physiological conditions. It is, therefore, proposed for different biomedical and pharmaceutical applications. In particular, due to its gelling properties, it can be used to form a polymeric network able to preserve biomolecules from harsh environments. The current study was designed to investigate the influence of different probes on the rheological properties of gels made up of zein, in order to characterize the systems as a function of the polymer concentration. Four model compounds characterized by different physico-chemical properties were entrapped in zein gels, and different behaviors (viscoelastic or pronounced solid-like characteristics) of the systems were observed. Zein-based gels showed various release profiles of the encapsulated compounds, suggesting that there are different interaction rates between the probes and the polymeric matrix.